Glycemic variability of glycated hemoglobin in patients with type 2 diabetes mellitus and the risk of cardiovascular diseases: a latest systematic review and meta-analysis - Wu, Chan; Li, Aijing; Zhu, Qingyi; Guo, Jingyi; Li, Yincheng; Gu, Xin; Sun, Anning; Wei, Maoying; Gong, Yanbing (Frontiers in Endocrinology, 2025)
ObjectiveGlycated hemoglobin (HbA1c) variability is a crucial indicator for evaluating the stability of long-term glycemic control in patients with diabetes mellitus. This study aimed to clarify the association between HbA1c variability and the risk of incident cardiovascular disease (CVD) and mortality in patients with type 2 diabetes mellitus (T2DM) through a systematic review, thereby providing evidence-based support for the early prevention of adverse cardiovascular events in T2DM patients.MethodsWe systematically searched the PubMed, Web of Science, The Cochrane Library, and Embase databases for studies on the association between HbA1c variability and cardiovascular outcomes in patients with T2DM, published from the establishment of each database up to August 5, 2025. Cardiovascular outcomes included the incidence of CVD and CVD-related mortality. Two researchers independently conducted literature screening, data extraction, and risk of bias assessment. Meta-analysis was performed using Review Manager 5.3 software, with hazard ratio (HR) or odds ratio (OR) as the effect size.ResultsA total of 31 cohort studies were included, covering 545,956 participants from 13 countries and regions. The results of the meta-analysis showed that a higher coefficient of variation (CV) of HbA1c was significantly associated with an increased risk of cardiovascular events (HR = 1.32, 95% CI: 1.18–1.49, P < 0.00001; OR = 1.39, 95% CI: 1.22–1.57, P < 0.00001), and also significantly elevated the risk of mortality (HR = 1.35, 95% CI: 1.16–1.57, P < 0.00001). The standard deviation (SD) of HbA1c was also significantly correlated with a higher risk of cardiovascular events (HR = 1.27, 95% CI: 1.17–1.38, P < 0.00001; OR = 1.30, 95% CI: 1.07–1.57, P = 0.008) and a significant increase in mortality risk (HR = 1.27, 95% CI: 1.17–1.37, P<0.00001). The hemoglobin glycation index (HGI) was significantly associated with the risk of cardiovascular events in terms of HR (HR = 1.36, 95% CI: 1.14–1.62, P = 0.0006), but no statistical significance was observed in terms of OR (OR = 1.47, 95% CI: 0.98–2.20, P = 0.06). In contrast, the HbA1c variability score (HVS) showed no significant association with either the risk of cardiovascular events (HR = 1.31, 95% CI: 0.97–1.78, P = 0.08) or mortality risk (HR = 1.00, 95% CI: 0.76–1.31, P = 1.00).ConclusionsHbA1c variability is positively associated with the risk of adverse cardiovascular events in patients with T2DM. Among the indicators of HbA1c variability, the coefficient of variation (CV), standard deviation (SD), and hemoglobin glycation index (HGI) can serve as significant predictors for the risk of cardiovascular disease (CVD) occurrence and mortality. However, the HbA1c variability score (HVS) did not show significant predictive value in this study.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251132972.